Analisis Pendapatan Rumah Tangga Sistem Integrasi Sapi Kelapa Sawit (SISKA) Pola Semi Intensif di Kecamatan Pangkalan Lesung Kabupaten Pelalawan - Intan Feronika; Yusmini Yusmini; Jum’atri Yusri (Politeknik Pertanian Negeri Payakumbuh, 2020)
Cow-oil palm integration system is an activity that combines two or more farms with the aim of increasing profits. The application of a system of integration between cattle and oil palm has a huge impact on farmers, especially improve the management of oil palm plantation and effective cattle management for increasing productivity. This researchy aims to analyze the income structure and income distribution of SISKA program household farmers. This research was conducted in Pangkalan Lesung district Pelalawan regency. The methods used in this research is a survey method and research respondents taken as many as 40 farmers in a census.The results showed that household income is sourced from the primary income SISKA and sideline income. The main income of the farmer SISKA sourced from farming the land for palm oil SISKA and non SISKA, SISKA farmers sideline income while sourced from cattle business, trade business, civil servant (PNS), and Councilor. Oil Palm ventures SISKA earn an average income of Rp 25.350.084,69/2 ha/year (55.48percents), from oil palm farming on non which is Rp12.547.756,82/ average land area 1.03 ha/year (27.46percents). For a side income from livestock farms obtain average income of Rp 3.768.200,52/year (8.25percents). As for the revenue from non-agricultural get the Rp 3.905.312 .50/year (8.81percents). The Gini Index of Ratio of farmers is at a low inequality of 0.03, meaning that oil palm farming activities and cattle activities are homogeneous.